Risk assessment of persistent organic pollutants in fishes from Pakistan and its neighbouring countries - Sehrish Kalsoom; Zahida Nasreen (Journal of Fisheries, 2019)
Persistent Organic Pollutants (POPs) include a wide range of compounds including dichlorodiphenyltrichloroethanes’ (DDTs), hexachlorocyclohexanes (HCHs), polybrominated diphenyl ethers (PBDEs) and polychlorinated biphenyls (PCBs). These pollutants are present everywhere on earth i.e. soil, water and air. Their excessive use has adversely affected all ecosystems and their components including marine and freshwater, wildlife and human health. Although the use of POPs has been banned in many countries but they are still in use in many developing countries. This paper presents the sources and distribution of different POPs with special reference to their adverse effects and possible routes of contamination. Moreover, accumulation of these persistent pollutants in different body parts of fishes from major locations in Pakistan and its neighbouring countries (India, China and Iran) has been presented which exhibits their risk assessment for these important bioindicators of aquatic environments.